Iron isotope transformations in the meromictic Lake Cadagno. (15th June 2019) - Ellwood, Michael J.; Hassler, Christel; Moisset, Sophie; Pascal, Ludovic; Danza, Francesco; Peduzzi, Sandro; Tonolla, Mauro; Vance, Derek
Abstract: The iron isotope composition of sedimentary deposits is a key tool for tracking changes in the biogeochemical and redox conditions of modern and geologically ancient aquatic systems. The use of iron isotopes to reconstruct oxic, anoxic and redox conditions is based on iron isotope fractionation associated with the iron(II)–iron(III) redox reaction and the formation of various iron oxy, hydroxy and sulfur species. However, the degree of iron isotope fractionation varies within the sedimentary record, and the processes leading to isotope fractionation within aquatic systems also vary. Here we investigate iron isotope fractionation within the water column of Lake Cadagno, Switzerland. Lake Cadagno is a 21 m deep alpine meromictic lake that is permanently stratified. It has two chemically distinct water layers: an oxic mixolimnion separated by a narrow chemocline from an anoxic monimolimnion. The chemocline is located across a narrow band between 10 and 13.5 m and is defined by steep chemical gradients in dissolved oxygen, redox potential, nutrients (nitrite + nitrate, ammonia), dissolved and particulate trace metals (iron and manganese) and sulfur species. Iron isotope determination ( 56 Fe/ 54 Fe ratio; expressed as δ 56 Fe) of both dissolved (δ 56 Fedissolved ) and particulate (δ 56 Feparticulate ) iron reveals a sharp transition within the chemocline with a heavy δ 56 Fedissolved value (+0.75‰) at 11.5 m and light δ 56 Fedissolved value (−0.61‰) below at 12 m. The large shift in δ 56 Fedissolved occurs where anoxygenic phototrophic bacteria become abundant. Modelling of the dissolved iron isotope fractionation within the chemocline produced fractionation factors of −0.60‰ (kinetic model) and −1.52‰ (equilibrium model) assuming a two-step process involving iron oxidation followed by precipitation. Changes in the isotope composition of particulate iron with depth are subtler to that of dissolved iron, with slightly lighter values (−0.18‰) above the chemocline and slightly heavier values (+0.13‰) below. The production of reduced iron(II) within and below the chemocline is likely coupled to dissimilatory iron(III) reduction and dissolution reactions associated with sinking iron(III) oxy and hydroxy species. These processes lead to a peak in dissolved iron concentrations at 12.5 m. The decline in dissolved iron concentration below this depth and its change in isotope composition is consistent with the formation of iron sulphide species, e.g. mackinawite, under mildly euxinic conditions. Overall our results indicate that variations in δ 56 Fedissolved likely involve a combination of biotic and abiotic processes with biological mixing enhancing the rate at which iron(II) is transferred across the chemocline. The observed isotope transformation of dissolved iron across the chemocline of Lake Cadagno may make it a reasonable analogue to past shallow-water systems with mild euxinia.